Improving grid strength in a wide‐area transmission system with grid forming inverters. Issue 2 (3rd May 2022) - Mayer, Peter F.; Gordon, Mark; Huang, Wen‐Cheng; Hardt, Christian
Abstract: This paper summarizes Electromagnetic Transient (EMT) simulation studies using PSCAD/EMTDC undertaken to evaluate the capability and suitability of commercially available large scale Grid Forming Inverters (GFMI) to dampen oscillations in a real bulk power transmission network. Faults and a range of grid voltage oscillation frequencies are tested on GFMI and synchronous condenser (SC) models using single source equivalent network model and comparisons of transient, post fault and oscillatory rejection tests are presented. A critical credible fault in the West Murray Zone (WMZ) was simulated on a wide‐area EMT model of the Australian National Electricity Market (NEM) to show the effectiveness of GFMI in providing system strength services and improving damping of network sub‐synchronous control interactions (SSCI). Two scenarios were examined: Direct replacement of existing centralized synchronous condensers in the WMZ of the NEM, and a decentralized distribution of GFMI in the transmission network (treated as expansion or repowering solution for existing grid following inverter equipped solar farms). Simulation results show that commercially available GFMI are a viable option for improving system strength in a practical transmission system with a high proportion of Inverter Based Resources (IBR).